The Rohingya Crisis: Socio-economic and Security Impacts on Bangladesh - Akter, Sinzina (The Jahangirnagar Review Part-C, 2024)
The Muslim Ethnic group who used to live in the north-western part of the Rakhine state of Myanmar is known as Rohingya. Myanmar does not consider them as its citizens. The Myanmar military has conducted periodic ethnic cleansing with “a genocidal intent” to uproot the Rohingya from the Rakhine state, which led to the forcible displacement of the Rohingya in Bangladesh. The Rohingya influx has caused socio-economic and security effects on Bangladesh such as rise of extremist groups, drug trafficking, armed violence, human trafficking, rises in prices, environmental degradation etc. The repatriation of the Rohingyas is very important. Because the Rohingya influx is creating many problems. With the help of the major powers and powerful countries, the repatriation process will be successful. Otherwise 1.1 million Rohingyas living in Bangladesh will add more problems to this developing country.